Pola Hidup Sehat Mahasiswa di Masa Pandemi Covid-19: Studi Kasus di Kelurahan Tombolo, Kabupaten Gowa - Muh. Akram Lawarani (Emik, 2021)
The Covid-19 pandemic, which has been endemic since the end of 2019 until the end of 2020, has claimed many victims. One way to prevent the spread is by implementing a healthy lifestyle that may increase immunity and endurance, and many of those infected are people aged 50 years and over who have a history of chronic diseases and congenital diseases. Therefore, many young people feel they don't need to be afraid of Covid-19 and don't pay too much attention to a healthy lifestyle. Students who are between late teens and early twenties are a busy age, both in terms of academic activities and non-academic activities, often making them neglect a healthy lifestyle. This article deals with healthy life pattern among college students. This qualitative study was conducted in the village of Tombolo, Gowa Regency between October and December 2020. This location was chosen because based on data, those infected with Covid-19 in this location are relatively low. Data collection was carried out by in-depth interviews with 10 college student, consisting of five men and five women, aged between 19 and 23 years. The study shows that in 2016 the government had launched the Healthy Living Community Movement (GERMAS). Although the government has recommended prevention of Covid-19 with the 3M movement (washing hands, wearing masks, maintaining distance), GERMAS is revealed in the form of activities that support more complex Covid-19 prevention which include: washing hands with soap, eating balanced nutritious food, exercise and adequate rest, maintain environmental hygiene, do not smoke, drink eight glasses of mineral water/day, eat perfectly cooked food and do not eat meat from animals that have the potential to transmit, if fever and shortness of breath go to a health facility immediately, wear a mask if cough or cover your mouth with the inside of your upper arm, and pray. Students' perceptions of a healthy lifestyle are related to how a person pays attention to eating/drinking, physical activities (exercise), and their resting time to avoid Covid-19. These perceptions are intertwined with the healthy lifestyle applied by students, in the form of personal hygiene patterns, eating patterns, exercise patterns, and resting patterns.